The Principle of Equity in the General Environmental Law: Ethics and Environmental Justice - Lanegra Quispe, Ivan (2009)
This paper addresses the relationship between ethics and environmental law from the analysis of the principle of equity included in the General Environmental Law. In this sense, the author begins by developing the concept of "environmental justice" and its connection with the principle of equity. Secondly, he analyzes this principle within the framework of public policy development, emphasizing that we are facing a challenge due to the fact that its implementation includes integration into the development agenda and the fight against poverty. The author questions the neutrality of state action and positions the idea of assuming an adequate distribution of environmental burdens and risks among citizens. Along these lines, the author defines and proposes the adoption of mechanisms aimed at incorporating the ethical dimension into the development of environmental law in Peru.